2011
DOI: 10.1158/1535-7163.mct-11-0220
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Delivery of MicroRNA-7–Expressing Plasmid Overcomes Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor-Resistance in Lung Cancer Cells

Abstract: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKI) have been strikingly effective in lung cancers harboring activating EGFR mutations. Unfortunately, the cancer cells eventually acquire resistance to EGFR-TKI. Approximately 50% of the acquired resistance involves a secondary T790M mutation. To overcome the resistance, we focused on EGFR suppression using microRNA-7 (miR-7), targeting multiple sites in the 3 0 -untranslated region of EGFR mRNA. Two EGFR-TKI-sensitive cell lines (PC-9 and H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 43 publications
4
75
0
Order By: Relevance
“…miR-7 expression was found to be repressed in lung cancer tissues (7,14). Moreover, miR-7 was able to suppress the growth and metastatic potential of human lung cancer cells in vitro (15). Our previous studies also demonstrated that overexpression of miR-7 reduced the growth and metastasis of human lung cancer cells in vivo (16,17).…”
Section: Introductionmentioning
confidence: 79%
“…miR-7 expression was found to be repressed in lung cancer tissues (7,14). Moreover, miR-7 was able to suppress the growth and metastatic potential of human lung cancer cells in vitro (15). Our previous studies also demonstrated that overexpression of miR-7 reduced the growth and metastasis of human lung cancer cells in vivo (16,17).…”
Section: Introductionmentioning
confidence: 79%
“…The main mechanisms of acquired resistance to these drugs include secondary mutations in EGFR, such as the gatekeeper T790M mutation, detected in approximatively 50% of resistant cases; and amplification of the MET oncogene [98], observed in 5-20% of resistant cases [99]. This resistance can be overcome by EGFR inhibition by miR-7, which targets three sites in the 3'-untranslated region of EGFR mRNA [100]. Recent evidence showed that several miRNAs can be involved in resistance to different drugs targeting EGFR ( Table 2).…”
Section: Mirnas and Resistance To Targeted Therapy In Nsclcmentioning
confidence: 99%
“…58 Interestingly, liposomal delivery of miRNA-7-expressing plasmid overcame EGFR-TKI resistance in lung cancer cells. 59 Solid LNPs loaded with anti-miRNA oligonucleotides (AMOs) increased the inhibitory effect of miRNA-21 on the proliferation, migration, and invasion of human lung cancer cells. 60 However, the further in vivo data were not reported in the above two studies.…”
Section: Systemic Ncrna Delivery Strategies In Lung Cancer Treatmentmentioning
confidence: 99%